2019
DOI: 10.1371/journal.pone.0222201
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccine based on conserved HA-peptides induces strong immune response and rapidly clears influenza virus infection from vaccinated pigs

Abstract: Swine influenza virus (SIVs) infections cause a significant economic impact to the pork industry. Moreover, pigs may act as mixing vessel favoring genome reassortment of diverse influenza viruses. Such an example is the pandemic H1N1 (pH1N1) virus that appeared in 2009, harboring a combination of gene segments from avian, pig and human lineages, which rapidly reached pandemic proportions. In order to confront and prevent these possible emergences as well as antigenic drift phenomena, vaccination remains of vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 72 publications
0
34
0
Order By: Relevance
“…DNA vaccines based on different gene combinations (mainly HA) demonstrated good degrees of protection against homologous challenge (70,71,(97)(98)(99). Needle-free and IM delivery methods were tested to be successful, but recent studies evaluated needlefree delivery as it was claimed to be safer and easier to administer for large scale vaccination (97)(98)(99). The combination of priming with a DNA vaccine and boosting with an inactivated vaccine conferred significantly better protection than only two doses of DNA vaccine (71).…”
Section: Other Non-replicative Vaccine Technologies Tested In Swinementioning
confidence: 99%
See 1 more Smart Citation
“…DNA vaccines based on different gene combinations (mainly HA) demonstrated good degrees of protection against homologous challenge (70,71,(97)(98)(99). Needle-free and IM delivery methods were tested to be successful, but recent studies evaluated needlefree delivery as it was claimed to be safer and easier to administer for large scale vaccination (97)(98)(99). The combination of priming with a DNA vaccine and boosting with an inactivated vaccine conferred significantly better protection than only two doses of DNA vaccine (71).…”
Section: Other Non-replicative Vaccine Technologies Tested In Swinementioning
confidence: 99%
“…The combination of priming with a DNA vaccine and boosting with an inactivated vaccine conferred significantly better protection than only two doses of DNA vaccine (71). However, heterologous cross protection was demonstrated even in presence of MDAs after two doses of DNA vaccine (99). The major handicap of those vaccines is that large doses of DNA and several vaccination doses were required to confer protection.…”
Section: Other Non-replicative Vaccine Technologies Tested In Swinementioning
confidence: 99%
“…In a subsequent challenge study, the vaccine was found to induce broad protection against heterologous PRRSV strains when administered twice to pigs [ 88 ]. In addition, a DNA vaccine based on conserved haemagglutinin (HA) peptides fused with flagellin, administered with a needle-free device, induced a strong immune response and rapidly cleared IAV from vaccinated pigs [ 89 ]. Maternally derived antibodies did not interfere with vaccination and there was a markedly increased mucosal IgA response in vaccinated pigs compared to non-vaccinated pigs [ 89 ].…”
Section: Compositionmentioning
confidence: 99%
“…Especially for intradermal applications, the dermis is an excellent site for vaccine delivery and rich in dendritic cells as well as lymph vessels which promote fast processing of incoming antigen ( http://www.positiveaction.info/pdfs/stars/pt_MSD1-8.pdf ). DNA vaccines appear to benefit from the intradermal route of administration [ 87 , 89 ]. Several commercial health companies have started to produce their own, individual intradermal injection devices, which can be used on company-specific vaccine bottles, and are sold to producers as package deals.…”
Section: Compositionmentioning
confidence: 99%
“…The version of a broad influenza DNA vaccine for production pigs may induce mostly antibodies (against HA and/or NA) to prevent infection and spread by shedding of influenza virus. In contrast, the version for humans should also contain genes for conserved internal virus proteins for additional CMI induction (against M and/or NP) to protect humans from disease and death, as well [ 66 , 86 , 87 ], and to provide potential cross-strain protection against newly arising drifted and shifted strains [ 5 ].…”
Section: Rationale For Further Development and Use Of Dna Vaccinesmentioning
confidence: 99%